Art as social commentary: visual syntax and meaning in Barbara Kruger’s collages - Canelo, Maria José (2016)
Barbara Kruger’s urban-inspired visual artworks articulate a critique of the discursive constructions both of the consumer and of consumption itself. A former designer and picture editor in magazines, Kruger resorts to the aesthetic and linguistic techniques of advertising and media to challenge the forms of knowledge of the consumption society. In line with Michel Foucault’s theory of discourse as a network of disciplinary knowledges, this paper will read consumption – the discipline –, and the consumer – the subject it produces –, against Kruger’s visual techniques in order to examine how the latter call into doubt the disciplining effect of consumption and, in particular, how Kruger’s reworking on the notion of the gaze is involved in that process. The analytical grid combines a Foucauldian perspective with the tools of visual discourse analysis proposed by Gunther Kress and Theo van Leeuwen.